The Transcription Cofactor Swi6 of the Fusarium graminearum Is Involved in Fusarium Graminearum Virus 1 Infection-Induced Phenotypic Alterations - Son, Moonil (Plant Pathol J, 2016)
The transcription cofactor Swi6 plays important roles in regulating vegetative growth and meiosis in Saccharomyces cerevisiae. Functions of Swi6 ortholog were also characterized in Fusarium graminearum which is one of the devastating plant pathogenic fungi. Here, we report possible role of FgSwi6 in the interaction between F. graminearum and Fusarium graminearum virus 1 (FgV1) strain DK21. FgV1 perturbs biological characteristics of host fungi such as vegetative growth, sporulation, pigmentation, and reduction of the virulence (hypovirulence) of its fungal host. To characterize function(s) of FgSWI6 gene during FgV1 infection, targeted deletion, over-expression, and complementation mutants were generated and further infected successfully with FgV1. Deletion of FgSwi6 led to severe reduction of vegetative growth even aerial mycelia while over-expression did not affect any remarkable alteration of phenotype in virus-free isolates. Virus-infected (VI) FgSWI6 deletion isolate exhibited completely delayed vegetative growth. However, VI FgSWI6 over-expression mutant grew faster than any other VI isolates. To verify whether these different growth patterns in VI isolates, viral RNA quantification was carried out using qRT-PCR. Surprisingly, viral RNA accumulations in VI isolates were similar regardless of introduced mutations. These results provide evidence that FgSWI6 might play important role(s) in FgV1 induced phenotype alteration such as delayed vegetative growth.